Pemetaan Tutupan Dan Penggunaan Lahan Menggunakan Drone Berbasis Sistem Informasi Geografis Di Desa Jonggon Jaya - Faldi, Muhammad Iqbal; Siswanto, Hari; Suhardiman, Ali; Ruslim, Yosep; Aquastini, Dwinita (Sekolah Tinggi Pertanian Kutai Timur, 2023)
Land use is the end result of any form of dynamic human intervention. How to find out the form of land cover and use by using drones. This study aims to map and identify land cover and land use and determine the accuracy value of aerial photo interpretation results of land cover and land use in Jonggon Jaya Village. The expected results provide information related to the results of making maps of land cover and use and provide information on the form of land cover and use. This research uses drones and ArcGis Pro software which produces land cover and land use classes that refer to the Indonesian National Standard (SNI) 7645-1: 2014 concerning Land Cover Classification. The results of mapping land cover and land use in Jonggon Jaya Village produced 29 land cover and land use classes obtained from the results of aerial photo interpretation. Industrial Plantation Forest (HTI) is the largest land cover and use with an area of 5096.30 Ha or 48.463% and rivers are the smallest land cover and use with an area of 0.32 Ha or 0.003%. The results of the accuracy test with the overall accuracy formula on the results of aerial photo interpretation are 95.18% of the data that matches the conditions on the ground or as many as 138 validation points that match the 145 overall validation points, while the interpretation error is 4.82% or 7 validation points.